Postkolonialne lęki w nawiedzonym domu. Motywy traumy i poszukiwania tożsamości w horrorze dla młodzieży "Nakarmię cię strachem" Trang Thanh Tran - Justyna Braszka (Zagadnienia Rodzajów Literackich, 2025)
The analysis presented in the article concerns the debut novel of young adult horror fiction entitled She Is a Haunting by Trang Thanh Tran. The interpretation of horror motifs in the novel is presented from the point of view of postcolonial studies. The plot of the novel centers on 17-year-old Jade Nguyen, who is an American of Vietnamese descent. The girl returns to her parents’ country to get money for college. She stays in an old house, which turns out to be haunted by ghosts. Jade begins her own investigation to unravel the mystery of the haunted house. She discovers the horrifying truth about the murderous activities of French colonizers in Vietnam. Tran uses the motif of horror to tell the story of the trauma of unrequited colonialism and the crimes associated with it. In addition, the book explores themes of the search for one’s own identity. The main story line is complemented by the contexts of historical and contemporary racism and the issue of migration and the Vietnamese diaspora in the United States. The text’s research questions revolve around the thematic symbiosis of horror with the postcolonial perspective (including in relation to young adult fiction literature): how does the novel address historical horror related to colonialism?; how can the creations of the haunted house and ghosts be interpreted in postcolonial terms? The article also presents the genre contexts of horror that appear on the pages of the novel. The analytical part of the text is preceded by a theoretical description, focusing on the relationship between young adult fiction and horror conventions.